The Processing of Visual and Phonological Configurations of Chinese One- and Two-Character Words in a Priming Task of Semantic Categorization - Ma, Bosen; Wang, Xiaoyun; Li, Degao (Frontiers in Psychology, 2016)
To separate the contribution of phonological from that of visual-orthographic information in the recognition of a Chinese word that is composed of one or two Chinese characters, we conducted two experiments in a priming task of semantic categorization, in which length (one- or two-character words), relation, prime (related or unrelated prime-target pairs), and SOA (47, 87, or 187 ms) were manipulated. The prime was similar to the target in meaning or in visual configuration in Experiment A and in meaning or in pronunciation in Experiment B. The results indicate that the two-character words were similar to the one-character words but were less demanding of cognitive resources than the one-character words in the processing of phonological, visual-orthographic, and semantic information. The phonological primes had a facilitating effect at the SOA of 47 ms but an inhibitory effect at the SOA of 187 ms on the participants’ reaction times; the visual-orthographic primes only had an inhibitory influence on the participants’ reaction times at the SOA of 187 ms. The visual configuration of a Chinese word of one or two Chinese characters has its own contribution in helping retrieve the word’s meanings; similarly, the phonological configuration of a one- or two-character word plays its own role in triggering activations of the word’s semantic representations